2004
DOI: 10.1115/1.1811113
|View full text |Cite
|
Sign up to set email alerts
|

Surface Finishing and Evaluation of Three-Dimensional Silicon Microchannel Using Magnetorheological Fluid

Abstract: A surface-finishing method for three-dimensional microchannel structures is proposed. The method utilizes magnetorheological fluid mixed with abrasives as a polishing tool. The influences of the process parameters on the material removal were investigated, and the surface topographies before and after finishing were compared. When a microchannel was finished by proposed method, the roughness of bottom and side surfaces of the silicon channel was reduced by a factor of 5–10, and the pressure drop of a gas flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This is accomplished through fine control of the magnetic field, which affects the force acting on the magnetic particles and determines the motion of the magnetic particles against the workpiece [8][9][10][11][12]. As typified by magneto-rheological fluid (MRF) polishing, magnetic field-assisted finishing has become widely used for ultraprecision finishing of optical components [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished through fine control of the magnetic field, which affects the force acting on the magnetic particles and determines the motion of the magnetic particles against the workpiece [8][9][10][11][12]. As typified by magneto-rheological fluid (MRF) polishing, magnetic field-assisted finishing has become widely used for ultraprecision finishing of optical components [13].…”
Section: Introductionmentioning
confidence: 99%
“…A disk-shaped permanent magnet is employed. For the sake of the gravity and the magnetic levitation force [16] , majority of abrasive particles within the MCF slurry move down towards the work surface. In addition, all of the clusters are collected forcibly by the magnetic attraction force and gathered in the area where the magnetic field is stronger.…”
Section: Polishing Principle and Experimental Rigmentioning
confidence: 99%
“…Pioneering studies regarding the mechanisms of glass removal using MR finishing can be found in [7][8][9]. Kim et al [10] performed preliminary experiments for the finishing of silicon-based structures with a group of micro-sized straight channels and obtained an optimized recipe together with the associated experimental conditions. During the MR finishing, the average channel height decreases by 2-3 mm with slight rounding at edges (or corners) formed inevitably.…”
Section: Introductionmentioning
confidence: 99%